PENGARUH INKUIRI TERBIMBING BERBASIS BLENDED LEARNING TERHADAP HASIL BELAJAR MAHASISWA CALON GURU PADA MATERI SISTEM PENCERNAAN MANUSIA - Dani Ramdani; Liah Badriah (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2019)
The purpose of this research was knowing the effect of guided inquiry learning based blended learning to student learning outcomes on human digestive system. This research was conducted in August 2016 until October 2016 in in Biology educational Department. The research method used true experiment method. The population of this research is all first semester students are four classes with 137 students. The sample used by 2 class taken by cluster random sampling that is A class with 32 students as experiment class and C class with 32 students as control class. Research instrument is a multiple choice learning outcomest test about human digetive System.Data analysis technique used test of difference of two mean (t-test) with ? = 0.05. Based on the results of research can be concluded that there is effect of guided inquiry learning based blended learning to student learning outcomes on human digestive system